The linguistic structure in the Iraqi civil laws - Nada Sami Nasser (QALAAI ZANIST JOURNAL, 2021)
Linguistic structures and their semantic impact on the drafting of the Iraqi Civil Law No. 40 of 1951, This research has included linguistic connotations as a basic structure in the drafting of the law in general and the Iraqi Civil Law No. (40) Of 1951 in particular, because of the role of the language in the drafting of the law because it is legislation dealing with special and general provisions governing the laws of society in all directions. The necessity of this research is to study the linguistic structures and their impact on the legal drafting and the importance of the above mentioned. The field of study in this research is the Iraqi civil law for its bases and diversity of subjects, which includes various civil contracts and their social life in their fields. The research includes the following structures the nominal sentence and its implications in the legal resist Syntactic schematization and postponing and its Implications on the legal register. The actual sentence and its implications in the legal register definiteness and indefiniteness and its implications on the legal rule. Subordination and their implications on the legal rule. Styles of negation, prohibition command and the question and its implications on the rule of law. The style of the condition and its implications on the legal rule. Styles of deletion and its implications on the legal rule. Styles of emphasis, assertion and its evidence on the legal rule. Finally, the conclusion includes the most important findings and recommendations that present this subject in our time and in the future.